Modified Emden Type Oscillator Equations with Exact Harmonic Solutions - YESSOUFOU, AKIM B; ADJAI, K K DAMIEN; AKANDE, JEAN; MONSIA, MARC DELPHIN (My University, 2022)
This paper is devoted to investigating the existence of exact harmonic solutions and limit cycles of certain modified Emden-type equations. The exact and general solutions obtained are in opposition to the predictions of classic existence theorems.
Keywords: Modified Emden-type equations; exact and harmonic solution; conservative nonlinear oscillator; algebraic limit cycles; existence theorem